2015
DOI: 10.1038/onc.2015.212
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of β1 integrins impairs DNA repair for radiosensitization of head and neck cancer cells

Abstract: β1 Integrin-mediated cell-extracellular matrix interactions allow cancer cell survival and confer therapy resistance. It was shown that inhibition of β1 integrins sensitizes cells to radiotherapy. Here, we examined the impact of β1 integrin targeting on the repair of radiation-induced DNA double-strand breaks (DSBs). β1 Integrin inhibition was accomplished using the monoclonal antibody AIIB2 and experiments were performed in three-dimensional cell cultures and tumor xenografts of human head and neck squamous c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 49 publications
4
71
1
Order By: Relevance
“…Additional noncanonical effectors of integrin signaling further include cross-talk with the CD44/hyaluronic acid axis, epidermal growth factor (EGF) receptor, and syndecan signaling (Yu et al, 2000;Ghatak et al, 2014;McQuade et al, 2006). In head and neck squamous cell carcinoma cells, β1 integrin activating FAK/JNK1 is essential for the repair of radiation-induced DSBs, and β1 integrin signaling supports expression of essential DNA repair genes, including Ku70/80 and Rad51 (Dickreuter et al, 2016;Ahmed et al, 2018). These data link integrin signaling to Treatment schemes for HT-1080 and MV3 tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Additional noncanonical effectors of integrin signaling further include cross-talk with the CD44/hyaluronic acid axis, epidermal growth factor (EGF) receptor, and syndecan signaling (Yu et al, 2000;Ghatak et al, 2014;McQuade et al, 2006). In head and neck squamous cell carcinoma cells, β1 integrin activating FAK/JNK1 is essential for the repair of radiation-induced DSBs, and β1 integrin signaling supports expression of essential DNA repair genes, including Ku70/80 and Rad51 (Dickreuter et al, 2016;Ahmed et al, 2018). These data link integrin signaling to Treatment schemes for HT-1080 and MV3 tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In consistent with this study, study on breast cancer showed that after treatment of cancer cell with taxol, the integrin α6 + CSC population is upregulated (111). Also, study of β1 integrins on head and neck cancer cell also support that integrins can act as potential cancer targets (112). However, specific integrins that is responsible to promote stemness, drug resistance, and metastasis of CSCs are yet to be determined (113).…”
Section: Therapeutic Strategies Of Lung Cscsmentioning
confidence: 94%
“…Moreover, targeting β1 integrin with an inhibitory antibody increased sensitivity to ionizing radiation and delayed the growth of HNSCC cell lines in 3D cultures and in xenografted mice [101], and has been shown to act by impairing repair of radiation-induced DNA double-strand breaks [102,103]. Combining the anti-β1 monoclonal antibody AIIB2 with a poly ADP ribose polymerase (PARP) inhibitor [102] or EGFR inhibitor [103] enhanced cytotoxicity and radiosensitization, providing better in vivo tumour control compared with monotherapy and irradiation in HNSCC models [103]. The combination of β1 and EGFR inhibition is proposed to act by preventing activation of MEK/ERK signalling, bypassing the effect of a single inhibitor [103].…”
Section: Integrins In Hnsccmentioning
confidence: 99%
“…With the exception of cilengitide, very limited preclinical studies have taken place so far [80,88,107]. The observations that inhibiting αv [55], αvβ3 [74], or β1 [101,102,103] increases sensitivity to irradiation is particularly significant for HNSCC as it suggests integrin-targeted therapy could be used as part of a chemoradiotherapy strategy for high risk disease.…”
Section: Applications Of Integrin-targeted Agentsmentioning
confidence: 99%